Social Movement of The Committee for The Enforcement of Islamic Sharia (KPSI) in Strengthening Islamic Values in West Sumatera - Husnul Qolbi; Aidinil Zetra; Asrinaldi Asrinaldi; Mhd. Fajri (Islam Realitas: Journal of Islamic and Social Studies, 2022)
This study describes the social movement of the West Sumatra Islamic Shari'a Enforcement Committee (KPSI) in the strengthening of Islamic values in West Sumatra for the 2014-2019. This period follow after the activities carried out by the West Sumatra KPSI after the rejection of the Lippo Superblock construction in 2013. This uses qualitative research with descriptive analysis with interview and documentation data collection methods. This research uses Islamic social movement theory and arrived at some important findings from this research. First, the mobilization of KPSI in strengthening Islamic values is not based on feelings of disappointment or dissatisfaction but as a form of concern towards the decadence of society. Second, political opportunities led KPSI West Sumatra to conduct da'wah (Islamic propogation). Third, the framing in which KPSI West Sumatra enganged in discourse became the target of mobilization in social movements based on the Qur'an and Sunnah. Fourth, the West Sumatran KPSI alliance or network has many alliances or networks to strengthen its movement.Penelitian ini mendeskripsikan gerakan sosial Komite Penegakan Syari'at Islam (KPSI) Sumbar dalam penguatan nilai-nilai Islam di Sumbar Tahun 2014-2019. Periode ini mengikuti kegiatan yang dilakukan oleh KPSI Sumbar pasca penolakan pembangunan Superblok Lippo pada tahun 2013. Penelitian ini menggunakan penelitian kualitatif dengan analisis deskriptif dengan metode pengumpulan data wawancara dan dokumentasi. Penelitian ini menggunakan teori gerakan sosial Islam dan sampai pada beberapa temuan penting dari penelitian ini. Pertama, mobilisasi KPSI dalam penguatan nilai-nilai Islam tidak didasarkan pada perasaan kecewa atau tidak puas tetapi sebagai bentuk kepedulian terhadap dekadensi masyarakat. Kedua, peluang politik mengantarkan KPSI Sumbar melakukan dakwah. Ketiga, framing di mana KPSI Sumbar berwacana menjadi sasaran mobilisasi dalam gerakan-gerakan sosial yang berbasis Al-Qur'an dan As-Sunnah. Keempat, aliansi atau jaringan KPSI Sumbar memiliki banyak aliansi atau jaringan untuk memperkuat gerakannya.